ABSENT BUT PRESENT: PROPAGANDA STRATEGIES OF THE JAPANESE OCCUPATION IN INDONESIA AS NARRATED IN KAMISHIBAI IN DJAWA BAROE MAGAZINE - Pasaribu, Rouli Esther (UI Scholars Hub, 2024)
This paper investigated the propaganda strategies in kamishibai (a paper play) story telling in Djawa Baroe Magazine. This study employed text analysis methods and propaganda theories from Jowett and Donnell on the seven kamishibai and found the following propaganda strategies. First, Western powers were portrayed negatively. Second, Japan was not explicitly featured in kamishibai stories. Third, local cultural elements in Javanese culture were used to convey propaganda messages. These findings indicate that entertainment media, such as kamishibai, can be used as propaganda media and subtly inserted using specific trivial strategies.